Variations in practices and outcomes of neonates with hypoxic ischemic encephalopathy treated with therapeutic hypothermia across tertiary NICUs in Canada - Beltempo, Marc; Wintermark, Pia; Mohammad, Khorshid; Jabbour, Elias; Afifi, Jehier; Shivananda, Sandesh; Louis, Deepak; Redpath, Stephanie; Lee, Kyong-Soon; Fajardo, Carlos; Shah, Prakesh S. (Journal of perinatology, 2022)
Objective To characterize variations in practices and outcomes for neonates with hypoxic-ischemic encephalopathy (HIE) treated with therapeutic hypothermia (TH) across Canadian tertiary Neonatal Intensive Care Units (NICUs). Study design Retrospective study of neonates admitted for HIE and treated with TH in 24 tertiary NICUs from the Canadian Neonatal Network, 2010–2020. The two primary outcomes of mortality before discharge and MRI-detected brain injury were compared across NICUs using adjusted standardized ratios (SR) with 95% CI. Results Of the 3261 neonates that received TH, 367 (11%) died and 1033 (37%) of the 2822 with MRI results had brain injury. Overall, rates varied significantly across NICUs for mortality (range 5–17%) and brain injury (range 28–51%). Significant variations in use of inotropes, inhaled nitric oxide, blood products, and feeding during TH were identified ( p values < 0.01). Conclusion Significant variations exist in practices and outcomes of HIE neonates treated with hypothermia across Canada.